Hubungan Religious Commitment Dengan Motivasi Belajar Pada Mahasiswa di UNISBA - Yuli Aslamawati; Eneng Nurlailiwangi; Ari Wulandari (SCHEMA (Journal of Psychological Research), 2011)
There is a phenomenon in UNISBA as a private Islamic University, the students show low motivation in their learning behavior process. Their effort to achieve a good grade without optimizing their capabilities, there is a tendency to choose an easy way, cheating and violating the university rules, these were associated to the low of a Religious Commitment. According to Glock & Stark. Religious Commitment is a religious consciousness includes the obedience to do the ritual believes, the faith, which that is application of their religious knowledge.The objective of this research are to obtain data and empirical picture about the relationship between religious commitment and the learning motivation among the students; and to see which dimension of religious commitment has greater closeness to learning motivation.This research used the correlation method. The measurement tool to describe the students Religious commitment used a scale based Glock and Stark theory; and the scale of student’s learning motivation is constructed based on the learning motivation theory from Gage and Berliner. 340 UNISBA’s students who are currently actively registered as the population in this study. The data gathering is based on cluster random sampling. The result was rs= 0.524; there was a positive correlation between the religious commitment and learning motivation among the students. It means the lower the religious commitment, the lower the motivation of learning among the students.